Somersaulting techniques used in high-scoring and low-scoring Roche vaults performed by male Olympic gymnasts - Takei, Y.; Dunn, J. H.; Blucker, E. P. (Journal of Sports Sciences, 2007)
The aim of this study was to compare the somersaulting techniques used in the 16 highest-scoring and 16 lowest-scoring Roche vaults. Our hypothesis was that the gymnasts performing the highest-scoring Roche vaults would demonstrate a better technique than those performing the lowest-scoring Roche vaults while on the horse (pushing off the horse more effectively), somersaulting (executing most of the required somersaults higher in flight), and landing (showing a greater control). A 16-mm motion picture camera, operating at 100 Hz, recorded the vaults during the official competition. The two-dimensional direct linear transformation was used for spatial reconstruction. The results of t-tests (P < 0.05) indicated that, compared with the low-scoring gymnasts, the high-scoring gymnasts had: (1) greater height of body centre of mass and a more fully extended body position at the horse take-off; (2) greater height of body centre of mass at the peak of post-flight, knee release, and touchdown on the mat; (3) greater horizontal and vertical displacements of body centre of mass, greater somersaulting rotation, and longer time from the knee release to mat touchdown; and (d) markedly smaller landing point deductions. In conclusion, a successful Roche vault is likely when the focus is on: (a) leaving the horse with a large vertical velocity in an extended body position to achieve a high trajectory of centre of mass by first extending the legs, then immediately pushing off the horse vigorously, using the muscles of the upper extremity; (b) grasping the knees immediately after the take-off from the horse, achieving the tightly tucked body position early during the ascent to the peak, and completing two-thirds of the required somersaults at a great height; (c) releasing the knees and extending the body above the top level of the horse; and (d) contacting the mat with a high body centre of mass position.